2004
DOI: 10.1515/bc.2004.054
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of calpastatin with calpain: a review

Abstract: Calpastatin is a multiheaded inhibitor capable of inhibiting more than one calpain molecule. Each inhibitory domain of calpastatin has three subdomains, A, B, and C; A binds to domain IV and C binds to domain VI of the calpains. Crystallographic evidence shows that binding of C to domain VI involves hydrophobic interactions at a site near the first EF-hand in domain VI. Sequence homology suggests that binding of A to calpain domain IV also involves hydrophobic interactions near the EF1-hand of domain IV. Neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(160 citation statements)
references
References 41 publications
3
154
1
2
Order By: Relevance
“…fast exchange was observed in the whole concentration range (data not shown), in accord with previous observations (reviewed in Refs. [1,3]). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…fast exchange was observed in the whole concentration range (data not shown), in accord with previous observations (reviewed in Refs. [1,3]). …”
Section: Resultsmentioning
confidence: 99%
“…For the first time, subdomains were defined as three well-conserved regions encoded by separate exons [26,29]. Other sequence alignment studies have suggested that A is located between S 12 and G 30 and C is between G 91 and T 104 [3]. These segments have been suggested as forming a-helices when bound to calpain, and interference with their helix-forming potential by point mutations does cause a drastic decrease in binding strength [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, regulation of protein-protein interactions changes the calcium requirements of calpains (Melloni et al, 2000a;Melloni et al, 2000b;Melloni et al, 1998;Melloni et al, 2000c;Michetti et al, 1991;Salamino et al, 1993), but their roles in activation are not clear. Finally, calpains are regulated by their best-known interacting partner, the endogenous calpain inhibitor calpastatin (Wendt et al, 2004). Although overexpression of calpastatin in cells can decrease calpain activity, escape from calpastatin is not Fig.…”
Section: Calpain Regulationmentioning
confidence: 99%
“…Besides the local calcium concentration, the endogenous protein-type inhibitor calpastatin plays an important role in the regulation of calpain activity (for a recent review see Wendt et al, 2004). Calpastatin is widely distributed in mammalian tissues.…”
Section: Introductionmentioning
confidence: 99%